2014
DOI: 10.1080/02687038.2014.881459
|View full text |Cite|
|
Sign up to set email alerts
|

Conversation focused aphasia therapy: investigating the adoption of strategies by people with agrammatism

Abstract: Background: A recent review of interaction (or conversation)-focused therapy highlighted the potential of programmes targeting the person with aphasia (PWA) directly. However, it noted the key limitations of current work in this field to be a reliance on single case analyses and qualitative evidence of change, a situation that is not unusual when a complex behavioural intervention is in the early stages of development and evaluation. Aims: This article aims to evaluate an intervention that targeted a PWA and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 28 publications
1
70
1
4
Order By: Relevance
“…It may therefore be useful to consider supporting and bolstering friendship circles, for example, through peer-support schemes or aphasia/stroke groups (Brown et al, 2013), adopting a more social approach to therapy (Pound et al, 2000), or exploring therapy approaches such as solution focused brief therapy which may increase confidence to engage socially (Northcott, Burns, Simpson, & Hilari, in press). Conversation partner programmes aimed primarily at spouses (Beeke et al, 2015) could potentially be adapted for supporting close friendships. Still, few research projects have specifically targeted friendship loss in an intervention study for this population.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…It may therefore be useful to consider supporting and bolstering friendship circles, for example, through peer-support schemes or aphasia/stroke groups (Brown et al, 2013), adopting a more social approach to therapy (Pound et al, 2000), or exploring therapy approaches such as solution focused brief therapy which may increase confidence to engage socially (Northcott, Burns, Simpson, & Hilari, in press). Conversation partner programmes aimed primarily at spouses (Beeke et al, 2015) could potentially be adapted for supporting close friendships. Still, few research projects have specifically targeted friendship loss in an intervention study for this population.…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
“…This work, alongside other research by Beeke and colleagues (e.g. Beeke et al 2011Beeke et al , 2014Beeke et al , 2015 thus explores improvements on qualitative and quantitative tests of conversational ability after the employment of conversation-based therapies. The focus of the research is on the interaction between the PWA and their partners, and indeed the conversation-focussed research to date has almost exclusively looked to promote and improve the inclusion of PWA in everyday (rather than clinical)…”
Section: Introductionmentioning
confidence: 99%
“…This intervention is thus not only focused on the individual with aphasia, but also strongly dependent upon the involvement of significant others. Research has demonstrated that individually adapted consultations, based on Conversation Analytical (CA) principles may positively change the communication situation for persons with aphasia (Beeke, Johnson, Beckley, Heilemann, Edwards, Maxim and Best, 2015). This finding gets further support from a research review on CA-informed aphasia interventions (Wilkinson, 2014) highlighting the benefits of this approach in relation to the everyday communication needs of people with aphasia and their significant others.…”
Section: Introductionmentioning
confidence: 87%